An Integrated Variable-Magnitude Approach for Accessibility Evaluation of Healthcare Institute Web Pages - Jinat Ara; Cecilia Sik-Lanyi; Arpad Kelemen (Applied Sciences, 2023)
The World Wide Web has become an important platform for sharing a wide array of information within the world community. In the post-COVID-19 scenario, the web become a primary source of information in the context of healthcare information dissemination. Healthcare institutions, such as hospitals and clinics, utilize this platform to provide services to reach their target users. It is essential to evaluate the web pages of healthcare institutions and compute their accessibility score for people with disabilities or special needs. This paper presents a variable-magnitude approach to compute the accessibility score of healthcare web pages, considering several requirements of people with disabilities. To compute the accessibility score through the proposed approach, we considered two different components and integrated them to compute the accessibility score through the proposed algorithm. The proposed approach was experimentally applied to sixteen healthcare institutes’ web pages in Hungary. Based on the experiment’s results and the received feedback from an accessibility specialist, a set of suggestions is provided to minimize the accessibility barrier and improve the accessibility score for people with disabilities to access web resources without difficulty. The main contribution of this work is in enhancing awareness of web platform accessibility for web practitioners to improve accessibility, so that people with disabilities can effectively access web resources.